2021
DOI: 10.1007/s41976-021-00059-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Shoreline Change Along the Coast of Lagos, Nigeria

Abstract: Shorelines and adjoining land remain an important site for the intensive interplay of socioeconomic development and natural processes. Unfortunately, the Lagos, Nigeria shoreline is always subjected to varied morphological changes in response to small (short term) and large-scale (long term) events as triggered by natural processes and human development. Thus, there is the need to accommodate these changes through a combination of the relative permanence of urban infrastructure and shoreline defense efforts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similar to the study of Adeaga et al [41], which assessed shoreline changes along the coast of Lagos, Nigeria, and utilized the findings to urge the integration of a coastal protection strategy, this study can be used to establish a management plan for protecting Metro Manila's urban coastline. In light of unfavourable changes in land use and the country's need for more sustainable development, this study of Metro Manila's urban coastline and LULC mapping will help decision-makers in identifying vulnerable zones, finding better solutions to existing coastline threats, and implementing policies that will protect the environment from further degradation.…”
Section: Discussionmentioning
confidence: 91%
“…Similar to the study of Adeaga et al [41], which assessed shoreline changes along the coast of Lagos, Nigeria, and utilized the findings to urge the integration of a coastal protection strategy, this study can be used to establish a management plan for protecting Metro Manila's urban coastline. In light of unfavourable changes in land use and the country's need for more sustainable development, this study of Metro Manila's urban coastline and LULC mapping will help decision-makers in identifying vulnerable zones, finding better solutions to existing coastline threats, and implementing policies that will protect the environment from further degradation.…”
Section: Discussionmentioning
confidence: 91%
“…Boye and Fiadonu [91] underlined that in the western region of Ghana, few areas of the shoreline are accreting, while most areas with a rocky shoreline are eroding at varying rates. Moreover, Adeaga et al [92] indicated that the Lagos, Nigeria, shoreline cumulatively recorded a mean rate change of 0.93 m/year, a mean erosion rate of −1.94 m/year, and a mean accretion rate of 4.84 m/year. The researchers again told us that the Victoria Islands recorded a mean erosion rate of −5.2 m/year and a mean accretion rate of 81.99 m/year over a 20-year period [92].…”
Section: Shoreline Change and Coastal Erosion Due To Natural Eventsmentioning
confidence: 99%
“…Similarly, in Lekki, Nigeria, Danladi et al [87] alluded to policymakers about the need for continuous inspection of the entire Lekki coast and the construction of environmentally friendly coastal defenses like dune barriers and sand replenishment. Again, in the Eti-Osa local government area of Victoria Island, Nigeria, Adeaga et al [92] mentioned to authorities the need to institute appropriate land use and land cover management plans for the area. Considering the serious nature of shoreline change and coastal erosion in Nigeria, Oloyede et al [99] suggested to coastal planners the practicability of their study in identifying the vulnerable portions of the Nigerian coast and subsequently aiding in the development of appropriate adaptation and mitigation plans.…”
Section: More Erosion Along Thementioning
confidence: 99%